Cosmic Rays - Szadkowski, Zbigniew (IntechOpen, 2018)
Measurements in present experiments have dramatically advanced our understanding of ultrahigh-energy cosmic rays. The suppression of the flux at the highest energies is now confirmed without any doubt, and strong limits have been placed on the photon and neutrino components. There are indications for a small, large-scale anisotropy both below and above the energy of the angle and for a correlation on smaller angular scales at E > 5.5*1019 eV. Around 3*1018 eV, there is a distinct change of slope with energy, and the shower-to-shower variance decreases. Interpreted with the leading LHC-tuned shower models, this implies a gradual shift to a heavier composition, and a number of fundamentally different astrophysical model scenarios have been developed to describe this evolution.